Characterization of Methicillin-Resistant Staphylococcus aureus, Vancomycin-Resistant Enterococci and Extended-Spectrum Beta-Lactamase-Producing Escherichia coli in Intensive Care Units in Canada: Results of the Canadian National Intensive Care Unit (Can-Icu) Study (2005–2006). Issue 3 (2008) - Zhanel, George G; DeCorby, Mel; Nichol, Kim A; Baudry, Patricia J; Karlowsky, James A; Lagace-Wiens, Philippe RS; McCracken, Melissa; Mulvey, Michael R; Hoban, Daryl J; The Canadian Antimicrobial Resistance Alliance (CARA),
Abstract : BACKGROUND: Methicillin-resistant Staphylococcus aureus (MRSA), extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli and vancomycin-resistant enterococci (VRE) are important hospital pathogens in Canada and worldwide. OBJECTIVES: To genotypically and phenotypically characterize the isolates of MRSA, VRE and ESBL-producing E coli collected from patients in Canadian intensive care units (ICUs) in 2005 and 2006. METHODS: Between September 1, 2005, and June 30, 2006, 19 medical centres participating in the Canadian National Intensive Care Unit (CAN-ICU) study collected 4133 unique patient isolates associated with infections in ICUs. Isolates of MRSA underwent mec A polymerase chain reaction (PCR) and Panton-Valentine leukocidin analysis; they were typed using pulsed-field gel electrophoresis. All isolates of E coli with ceftriaxone minimum inhibitory concentrations greater than or equal to 1 μg/mL were tested for the presence of an ESBL using the Clinical Laboratory Standards Institute double-disk diffusion method. Subsequently, PCR and sequence analysis were used to identify bla SHV, bla TEM and bl aCTX-M . Isolates of VRE were tested for the presence of van A and van B genes by PCR. RESULTS: Of the 4133 ICU isolates collected, MRSA accounted for 4.7% (193 of 4133) of all isolates. MRSA represented 21.9% (193 of 880) of all S aureus collected during the study; 90.7% were health care-associated MRSA strains and 9.3% were community-associated MRSA strains. Resistance rates for the isolates of MRSA were 91.8% to levofloxacin, 89.9% to clarithromycin, 76.1% to clindamycin and 11.7% to trimethoprim-sulfamethoxazole; no isolates were resistant to vancomycin, linezolid, tigecycline or daptomycin. ESBL-producing E coli accounted for 0.4% (18 of 4133) of all isolates and 3.7% (18 of 493) of E coli isolates. All 18 ESBL-producing E coli were PCR-positive for CTX-M, with bla CTX-M-15 occurring in 72% (13 of 18) of isolates. All ESBL-producing E coli displayed a multidrug-resistant phenotype (resistant to third-generation cephalosporins and one or more other classes of antimicrobials), with 77.8% of isolates resistant to ciprofloxacin, 55.6% resistant to trimethoprim-sulfamethoxazole, 27.8% resistant to gentamicin and 26.3% resistant to doxycycline; all isolates were susceptible to ertapenem, meropenem and tigecycline. VRE accounted for 0.4% (17 of 4133) of all isolates and 6.7% (17 of 255) of enterococci isolates; 88.2% of VRE had the van A genotype. Isolated VRE that were tested were uniformly susceptible to linezolid, tigecycline and daptomycin. CONCLUSIONS: MRSA isolated in Canadian ICUs in 2005 and 2006 was predominately health care-associated (90.7%), ESBL-producing E coli were all CTX-M producers (72% bla CTX-M-15 ) and VRE primarily harboured a van A genotype (88.2%). MRSA, ESBL-producing E coli and VRE were frequently multidrug resistant.